I am Albert Einstein - Meltzer, Brad.; Eliopoulos, Christopher (New York, N.Y. : Dial Books for Young Readers, an imprint of Penguin Group (USA) LLC, 2014)
Looks at the life and career of physicist Albert Einstein.
Includes bibliographical references.
Booklist
Horn Book
Booklist, June 2014
Horn Book, April 2015
3.2
Keywords: Einstein, Albert, -- 1879-1955 -- Juvenile literature; Einstein, Albert, -- 1879-1955.; Einstein, Albert, -- 1879-1955.; Physicists -- Biography -- Juvenile literature; Physicists; Physicists -- Biography; Biographies; Picture books